SARS-Cov-2 pandemic; what we know; effect on Orthopaedic services and academics - Pokhrel, Rohit Kumar (Nepal Orthopaedic Association Journal, 2020)
Corona viruses (CoVs) commonly cause relatively mild respiratory illness in humans and animals. However, within two decades, mankind experienced three highly pathogenic and deadly human corona virus infections, SARS-CoV (2002), MERS-CoV (2012) and SARS-CoV-2 (2019). Compared to mortality rate of SARS-CoV (> 10%) and MERS-CoV (35%), SARS-Cov-2 has a lower mortality rate but is more contagious. Current pandemicity of SARS-CoV-2, later named as COVID-19 by WHO in February 2020, has infected about 50 million and caused more than 1.2 million deaths in more than 200 countries, and about 200 thousands are infected and about one thousands died till date in Nepal, and the number is exponentially increasing, challenging health systems. Second wave of the infection in China, America and Europe has become a great challenge and the same in Nepal during winter may create an overwhelmingly unmanageable condition.